The red coral (Corallium rubrum) transcriptome: a new resource for population genetics and local adaptation studies - Pratlong, M.; Haguenauer, A.; Chabrol, O.; Klopp, C.; Pontarotti, P.; Aurelle, D. (Molecular ecology resources, 2015)
The question of species survival and evolution in heterogeneous environments has long been a subject for study. Indeed, it is often difficult to identify the molecular basis of adaptation to contrasted environments, and nongenetic effects increase the difficulty to disentangle fixed effects, such as genetic adaptation, from variable effects, such as individual phenotypic plasticity, in adaptation. Nevertheless, this question is also of great importance for understanding the evolution of species in a context of climate change. The red coral (Corallium rubrum) lives in the Mediterranean Sea, where at depths ranging from 5 to 600 m, it meets very contrasted thermal conditions. The shallowest populations of this species suffered from mortality events linked with thermal anomalies that have highlighted thermotolerance differences between individuals. We provide here a new transcriptomic resource, as well as candidate markers for the study of local adaptation. We sequenced the transcriptome of six individuals from 5 m and six individuals from 40 m depth at the same site of the Marseilles bay, after a period of common garden acclimatization. We found differential expression maintained between the two depths even after common garden acclimatization, and we analysed the polymorphism pattern of these samples. We highlighted contigs potentially implicated in the response to thermal stress, which could be good candidates for the study of thermal adaptation for the red coral. Some of these genes are also involved in the response to thermal stress in other corals. Our method enables the identification of candidate loci of local adaptation useful for other nonmodel organisms.